1999
DOI: 10.1037/0022-3514.76.2.229
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to cope with negative social identity: Predictions by social identity theory and relative deprivation theory.

Abstract: Predictions by social identity theory (SIT) and relative deprivation theory (RDT) concerning preferences for strategies to cope with a negative in-group status position were tested. The focus of the present research was a comparison of the theories regarding their differential patterns of prediction. For this purpose, a natural sample within a specific historical situation was investigated: East Germans after the German unification. First, the predictive power of SIT and RDT variables was tested separately. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
596
5
19

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 518 publications
(656 citation statements)
references
References 23 publications
36
596
5
19
Order By: Relevance
“…More recent research inspired by SIT (e.g., Crocker & Quinn, 2001;Ellemers & Barreto, 2001;Ellemers, Spears & Doosje, 1999;Mummendey, Kessler, Klink & Mielke, 1999;Simon, 2004) has examined the consequences of belonging to a social group which is perceived to be under threat. This work has revealed that members of threatened groups tend to have higher levels of identification with the ingroup, show higher levels of outgroup prejudice and/or ingroup favouritism, are more sensitive to status differentials between groups, and perceive the ingroup as being more homogeneous and more cohesive.…”
Section: Theoretical Accounts Of the Development Of Intergroup Attitumentioning
confidence: 99%
“…More recent research inspired by SIT (e.g., Crocker & Quinn, 2001;Ellemers & Barreto, 2001;Ellemers, Spears & Doosje, 1999;Mummendey, Kessler, Klink & Mielke, 1999;Simon, 2004) has examined the consequences of belonging to a social group which is perceived to be under threat. This work has revealed that members of threatened groups tend to have higher levels of identification with the ingroup, show higher levels of outgroup prejudice and/or ingroup favouritism, are more sensitive to status differentials between groups, and perceive the ingroup as being more homogeneous and more cohesive.…”
Section: Theoretical Accounts Of the Development Of Intergroup Attitumentioning
confidence: 99%
“…On the other hand; they may reject system justification beliefs, blame the system, demand retribution, and seek social change (Taylor & McKirnan, 1984). Research and theory indicates that permeability and legitimacy of group boundaries, intra versus intergroup social comparison, attributions, and identification with subgroup determine low status group member's reactions to denial of entry into high status groups (Ellemers, Baretto, & Spears, 1999;Tajfel, 1981;Mummendey, Kessler, Klink, Mielke, & Wenzel, 1999;Taylor & McKirnan, 1984). A minimal degree of permeability, perception of self as being close to the criteria of entry, system justification beliefs, seemingly acceptable reasons for exclusion, and blame attributions to in-group are associated with attempts at individual social mobility rather than group oriented attempts at social change (Hine & Montiel, 1999;Kappen & Branscombe, 2001;Sidanius & Pratto, 1999;Wright, Taylor, & Moghaddam, 1990).…”
Section: Characteristics Of the Intergroup Situationmentioning
confidence: 99%
“…Moreover, following from a social identity perspective, if groups compete over a self-defining characteristic, all things being equal, higher resource groups are likely to have an advantage in claiming valued characteristics as in-group identifying (e.g., Lemaine, 1974;Mummendey, Kessler, Klink, & Mielke, 1999; for reviews see Blanton, Christie, & Dye, 2002;Branscombe & Ellemers, 1998). If White and middle-class Americans are identified with health promotion through media campaigns or product advertising, or even as a consequence of easier access to health services, this in itself may reduce the salience of health promotion as a potential in-group attribute for other Americans who are racial or ethnic minorities or have low incomes.…”
mentioning
confidence: 99%